Split application of potassium improves yield and potassium uptake of rice under deficient soils - SHARMA, SEEMA; SINGH, JAGDISH (Journal of Soil and Water Conservation, 2021)
Potassium is involved in many vital plant functions improving grain quality, water and nutrient use efficiency, stress tolerance, energy-use efficiency, translocation of photosynthates and sugars from source to sink. The experimental site lies in the area of K-deficient region in the Punjab state, India. A two year (2016-17 and 2017-18) field experiment was conducted to assess the impact of split application of K on growth, yield and K uptake. The experiment comprising six treatments of K fertilizer application with four replications was laid out in a randomized complete block design. The results revealed significant improvement in growth and yield parameters of rice crop when numbers of splits were increased from single basal dose to two and three splits. The data further revealed a significant improvement in the total uptake of K(grain + straw) with three splits as compared to control application and single split application. The data on partial K budget revealed higher K removal where grain and biomass yield were higher in three split doses of K than that in control and single split application. The agronomic efficiency showed that the three split doses of potassium fertilizers may be recommended to achieve better yield and potassium use efficiency. The study highlights the need to study the complete potassium budget of crop for sustainable crop production.